2020
DOI: 10.33633/tc.v19i2.3326
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Perencanaan Jaringan Long Term Evolution (LTE) Pada Node B 4G di Kota Tangerang Selatan

Abstract: Kualitas jaringan Long Term Evolution (LTE) di Kota Tangerang Selatan masih kurang optimal, berdasarkan data hasil drive test nilai rata-rata RSRP dan SINR termasuk dalam kategori buruk. Hal tersebut dikarenakan jumlah site yang masih kurang, serta gedung-gedung yang menghalangi site. Perlu dilakukan perencanaan ulang untuk meningkatkan kinerja jaringan LTE di Kota Tangerang Selatan dengan melakukan perhitungan estimasi jumlah penduduk serta pengguna seluler pada tahun 2024, untuk mengetahui jumlah site yang d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…The results of this study are in line with research conducted by (Sirait, 2020) where after optimization showed an improvement in network quality by looking at network parameters, namely RSRP, SINR, and RSRQ. The percentage value of RSRP increased from 82.32% to 83.51%, for SINR decreased from 89.51% to 86.8%, and RSRQ [25]. Likewise, the study (Yuliana, 2019) also found that after carrying out the actual tuning improvements from the pre-determined sites, an increase in network conditions was obtained that was clearly superior to the previous condition, where the RSRP was not exactly -100dBm increased from 56.69% to 81.46% and SINR with a value of more than 0 dB also increased from 68.17% to 80.71% [26].…”
Section: A B a Bmentioning
confidence: 94%
“…The results of this study are in line with research conducted by (Sirait, 2020) where after optimization showed an improvement in network quality by looking at network parameters, namely RSRP, SINR, and RSRQ. The percentage value of RSRP increased from 82.32% to 83.51%, for SINR decreased from 89.51% to 86.8%, and RSRQ [25]. Likewise, the study (Yuliana, 2019) also found that after carrying out the actual tuning improvements from the pre-determined sites, an increase in network conditions was obtained that was clearly superior to the previous condition, where the RSRP was not exactly -100dBm increased from 56.69% to 81.46% and SINR with a value of more than 0 dB also increased from 68.17% to 80.71% [26].…”
Section: A B a Bmentioning
confidence: 94%
“…Regresi linier adalah model probabilistik yang menyatakan hubungan antara dua buah variabel yang dimana salah satu variabel mempengaruhi variabel lainnya. Dalam regresi linier sederhana hubungan dua variabel dapat dituliskan dalam bentuk persamaan linier [5]:…”
Section: Environment Pathloss Eksponen (N)unclassified
“…Bandwidth LTE adalah dari 1,4 MHz hingga 20 MHz, operator jaringan dapat memilih bandwidth yang berbeda dan memberikan layanan yang berbeda berdasarkan spektrum. Itu juga merupakan tujuan desain dari LTE yaitu untuk meningkatkan efisiensi spektrum pada jaringan, yang memungkinkan operator untuk menyediakan lebih banyak paket data pada suatu bandwidth [2].…”
Section: Pada Sisi Air Interface Lte Menggunakan Teknologiunclassified